IMPORTATION OF FACILITIES AND INFRASTRUCTURE PLANNING IN SMAN 1 SERBAJADI KECAMATAN SERBAJADI SERDANG BEDAGAI DISTRICT - Rifai, Muhammad; Suwandi, Suwandi; Ahmadsyah, Ahmadsyah (Universitas Dharmawangsa, 2020)
Implementation of facilities and infrastructure planning in improving the quality of education in SMA Negeri 1 Serbajadi. This research uses qualitative methods. The subject in this study is the implementation of facilities and infrastructure planning in SMA Negeri 1 Serbajadi. The informants in the research are Teachers and Students. how to interview, observation, and documentation. Data validity techniques using data triangulation and source triangulation. Data analysis techniques using interactive methods, data collection, data presentation, data reduction, and conclusion drawing. The results of the study note that (1) the implementation of facilities and infrastructure management in improving the quality of education in SMA Negeri 1 Serbajadi is carried out with Planning and Infrastructure Planning (Planning, namely a coordination meeting, determining the program, and determining the need for educational facilities and infrastructure. Organizing Facilities and Infrastructure (Organizing) covers the organizational structure of facilities and infrastructure management, division of job assignments/job descriptions, setting tools and practice materials, and organizing practical activities. Implementation of Facilities and Infrastructure Management (Actuating) in the form of procurement, maintenance, and elimination of facilities and infrastructure Control and Infrastructure (Controlling (carried out with an inventory. (2) Constraints of management of facilities and infrastructure in SMA Negeri 1 Multipurpose is a storage area that requires funds for expansion or repair, lack of administrative staff, especially for the management of facilities and infrastructure, and SMA Negeri 1 Serbajadi still experience a shortage of administrative staff